Negative interest rates, excess liquidity and bank business models: Banks' reaction to unconventional monetary policy in the euro area - Selva Demiralp; J. Eisenschmidt; T. Vlassopoulos (Koç University-TÜSİAD Economic Research Forum (ERF), 2017)
In June 2014 the ECB became the first major central bank to lower one of its key policy rates to negative territory. The theoretical and empirical literature is silent on whether banks' reaction would be different when the policy rate is lowered to negative levels compared to a standard reaction to a rate cut. In this paper we examine this question empirically by using individual bank data for the euro area to identify possible adjustments by banks triggered by the introduction of negative interest rates through three channels: government bond holdings, bank lending, and wholesale funding. We find evidence of a significant adjustment of banks' balance sheets during the negative interest rate period. Banks tend to extend more loans, hold more non-domestic government bonds and rely less on wholesale funding. The nature and scope of the adjustment depends on banks' business models.
Keywords: E43; E52; G11; G21; 330; negative rates; bank balance sheets; monetary transmission mechanism